2022
DOI: 10.1108/md-01-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

How empathetic leadership communication mitigates employees' turnover intention during COVID-19-related organizational change

Abstract: PurposeThe novel coronavirus (COVID-19) outbreak thrust a spotlight on organizational leaders and the challenges that employees face during periods of organizational change. The purpose of the current study is to examine the influence of empathetic supervisor communication on employee turnover intention and the mediating role of affective trust toward supervisors and employee–organization relationship (EOR) quality. Informed by the social exchange theory and EOR literature, the authors develop a model in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 99 publications
(220 reference statements)
1
32
0
Order By: Relevance
“…It is noteworthy that recent research on leadership communication has underscored the importance of empathetic leadership communication in fostering employee resilience and reducing turnover intentions during challenging circumstances (Wibowo and Paramita, 2022;Yue et al, 2023). Empathetic leadership communication entails leaders taking communicative actions to understand the emotional state of their followers and establish emotional connections by employing empathetic language (Kock et al, 2018;Mayfield and Mayfield, 2018).…”
Section: Leadership and Employee Health And Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that recent research on leadership communication has underscored the importance of empathetic leadership communication in fostering employee resilience and reducing turnover intentions during challenging circumstances (Wibowo and Paramita, 2022;Yue et al, 2023). Empathetic leadership communication entails leaders taking communicative actions to understand the emotional state of their followers and establish emotional connections by employing empathetic language (Kock et al, 2018;Mayfield and Mayfield, 2018).…”
Section: Leadership and Employee Health And Well-beingmentioning
confidence: 99%
“…Empathetic leadership communication entails leaders taking communicative actions to understand the emotional state of their followers and establish emotional connections by employing empathetic language (Kock et al, 2018;Mayfield and Mayfield, 2018). This involves leaders genuinely expressing concerns for the well-being of their followers (Mayfield and Mayfield, 2018;Yue et al, 2023). However, there remains a research gap in understanding how leaders at different hierarchical levels can effectively communicate such concerns and, ideally, enhance the well-being of their followers.…”
Section: Leadership and Employee Health And Well-beingmentioning
confidence: 99%
“…Linking supervisor verbal aggressiveness, EORs and employee CWB Previous research has suggested that supervisory communication is an important factor in shaping employees' perceptions of their relationship with their organization (Men et al, 2022). For example, Yue et al (2022b) found that empathetic communication by supervisors during times of organizational change had a positive impact on employees' interpersonal trust toward their supervisors, which in turn influenced their organizational trust, commitment, satisfaction and control mutuality.…”
Section: Employee-organization Relationshipsmentioning
confidence: 99%
“…We propose that employee thriving and employee empowerment as direct outcomes of servant leadership, which in turn leads to a positive perception of organizational reputation. It is important to note that this study examines supervisors “practice of servant leadership as they are a powerful force in shaping followers” psychological reactions and overall evaluation of their organization (Yang and Mossholder, 2010; Yue et al , 2022). While middle or lower-level supervisors do not dictate the strategic direction of an organization, they can have a significant impact on their followers by observing their behaviors and responding to their needs and desires (Jokisaari and Vuori, 2018; Yue et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the crucial role of managers in projecting a desired organizational image to employees (Scott and Lane, 2000;Yue et al, 2022) and the preceding logic justifying how each dimension of internal reputation can be connected to servant leadership, we proposed the following hypothesis.…”
Section: Linking Servant Leadership and Perceived Organizational Repu...mentioning
confidence: 99%